The Influence of Employee Engagement and Organizational Culture on Employee Performance through Job Satisfaction at Mis Al-Hamid Banjarmasin - Novi Saparina (PT. Hanken Sukses Jaya, 2021)
This study aims to determine the effect of Employee Engagement and Organizational Culture on Employee Performance through Job Satisfaction at Mis Al-Hamid Banjarmasin. The object of this research is all employees at Mis Al-Hamid Banjarmasin. The method in this study used quantitative methods. Data collection methods were carried out through questionnaires distributed to the population of this study, namely all 53 employees at Mis Al-Hamid Banjarmasin. Data analysis using F test and t-test. The results of this study indicate that the employee engagement variable has a significant effect on employee performance, partially employee engagement has a substantial impact on job satisfaction, organizational culture partially has an enormous impact on employee performance, corporate culture partially has a significant effect on job satisfaction, employee engagement and culture. The organization simultaneously has a substantial effect on teacher performance through job satisfaction.